Obsidian and Early Cultural Contact in the Near East (I. Introduction; II. Division of Analyses into Groups; III. The Sources; IV. Historical Context of Obsidian Artifacts; V. Trade and Cultural Context) - Renfrew, Colin (1966)
for 1966 = NS 32.